1998
DOI: 10.1037/h0087839
|View full text |Cite
|
Sign up to set email alerts
|

The ethical practice of psychology in a managed-care framework.

Abstract: With the rise of managed healthcare, psychologists face new challenges to their professional ethics. This article examines the dilemmas posed by managed care in three areas: client care; the handling of patient data; and issues surrounding membership in a managedhealthcare organization. Case examples of ethical dilemmas and strategies for dealing with these challenges are presented. In an attempt to summarize the strategies used to cope with the ethical dilemmas presented in the case examples, global solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The person who needs a more prolonged session or the organization that pays me?'' This dilemma, which is present across a variety of cultural contexts, organizations, and intervention modalities (Amundson & Borgen, 2000;Bilynsky & Vernaglia, 1998;Scaturo, 2005;Toomer, 1980), showed how the global modern-day economic forces influence the dilemmas in psychological practice, which in turn impact the nature of psychologists' working relationships with clients and the type of service provided. This is the case for our participants: The higher frequency of this dilemma in the subgroup work/employment setting can be explained by the increasing incompatibility between rates of productivity and clients' needs resulting from the fact that data from this investigation were collected over a period of economic recession that increased both the number of unemployed persons and the pressure on PES and NOS to help these persons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The person who needs a more prolonged session or the organization that pays me?'' This dilemma, which is present across a variety of cultural contexts, organizations, and intervention modalities (Amundson & Borgen, 2000;Bilynsky & Vernaglia, 1998;Scaturo, 2005;Toomer, 1980), showed how the global modern-day economic forces influence the dilemmas in psychological practice, which in turn impact the nature of psychologists' working relationships with clients and the type of service provided. This is the case for our participants: The higher frequency of this dilemma in the subgroup work/employment setting can be explained by the increasing incompatibility between rates of productivity and clients' needs resulting from the fact that data from this investigation were collected over a period of economic recession that increased both the number of unemployed persons and the pressure on PES and NOS to help these persons.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we aim to compare two groups of career counsellors according to the main settings where counselling occurs: employment and education. This goal is supported by research that emphasised the role of context in the experience of dilemmas (Arcaya, 2008;Bilynsky & Vernaglia, 1998;Toomer, 1980), as well that conducted by Sultana and Watts (2006), who suggested that despite similarities between career guidance in educational setting and in PES, there are also substantial differences.…”
Section: Career Counsellors' Dilemmasmentioning
confidence: 94%
See 1 more Smart Citation
“…These steps will act as a foundation for clinicians' continual communication with managed care personnel when a clinician, for example, seeks reimbursement for a test that was administered without preauthorization. Bilynsky and Vernaglia (1998) suggested five strategies for managing ethical dilemmas and working within a managed care setting: understanding of managed care polices, clear communication with the client, adequate training and education in managed care polices and how to work within a managed care system, increased advocacy by clinicians, and involvement within MCOs.…”
Section: Collaboration With Third-party Payersmentioning
confidence: 99%
“…Even though progress was made regarding cost containment, quality of care was not emphasized to the extent necessary (McCarthy, Gelber, & Dugger, 1993). As costs in health care increased, so did the number of restrictions placed by insurers on reimbursement for mental health services (Austad, Hunter, & Morgan, 1998;Bilynsky & Vernaglia, 1998;Cooper & Gottlieb, 2000). As a result, providers and consumers expressed concerns about diminishing access to needed services as health care service delivery moved from traditional fee-for-service providers (e.g., consumers purchased insurance from a commercial carrier, paid a deductible, and chose their physician separately; Huber, 1995) to managed care providers (Huff, 2000).…”
Section: Effectiveness and Impact Of Managed Carementioning
confidence: 99%